Health Monitoring System Using Wireless Sensor Network (WSN) and LabVIEW - Abhimanyu Singh; Akash Gupta (Journal of Power Electronics and Devices, 2022)
With the development of technology, many researchers have developed various designs for patient health monitoring systems, making patient health monitoring one of the fields that is expanding very quickly today. The Internet of things is one of the recently emerging fields due to the extensive use of the internet, and many people have been able to combine it into many applications. The IoT-based patient health monitoring system with LabVIEW and Wireless Sensor Network is described in this study (WSN). The system can capture a patient’s physiological parameters, transmit them wirelessly via Xbees, display the sensor data on LabVIEW, and publish that data to a web server so that other healthcare providers can view, control, and continuously monitor the patient from a distance using internet connectivity.